Interventions to reduce social isolation and loneliness among minority ethnic populations in OECD countries: A scoping review. - Emmanuel Sunday Nwofe; Amirah Akhtar; Sahdia Parveen; Karen Windle (PLoS ONE)
Background Social isolation and loneliness (SIL) are complex issues that impact mental and physical wellbeing and are significant public health concerns. People from minority ethnic backgrounds living in Organisation for Economic Cooperation and Development (OECD) member states may be particularly vulnerable to experiencing SIL. This is due to various challenges associated with life in foreign countries, including cultural differences, settlement issues, low incomes, and discrimination. While many interventions have been developed to address SIL in the general population, there is little information about interventions designed for minority ethnic populations in OECD countries. Our study aimed to 1) Investigate existing interventions for minority ethnic communities in OECD countries; 2) Assess how these interventions are conceptualised to increase awareness of SIL risks on health factors.3) Explore culturally sensitive approaches in these interventions, and 4) Identify the most effective interventions in reducing SIL in minority ethnic populations. Methods and findings We searched Medline, APA PsycINFO, Psychology and Behavioural Sciences Collection, CINAHL, Web of Science, and Scopus from their inception to September 19th, 2023, and registered the scoping review at https://osf.io/fnrvc. Our search yielded 10,479 results, of which 12 studies were included: five RCTs, six non-randomized quasi-experimental studies, and one qualitative study. Interventions were grouped into four main categories: social facilitation, befriending, leisure and skills development, and health education programmes. While only a few interventions targeted minority ethnic populations specifically, our findings highlight the potential of culturally sensitive interventions in reducing social isolation and loneliness among minority ethnic communities in OECD countries. However, given the type and extent of evidence, it is still unclear which interventions are superior in reducing SIL in minority ethnic populations in OECD countries. Further research is necessary to understand which activities may be most effective for which communities. Such interventions should be designed and tailored to account for the broader risk implications of SIL to raise awareness of the population's peculiar health risk profile. Discussion Interventions designed to address SIL among minority ethnic groups in OECD member states are scarce and have not been designed to account for the health risks profile of the population. Integrated research designs involving groups linked with minority ethnic populations are needed to link individual, community, and societal factors alongside population risk profiles for increased recognition of SIL as an important health factor.